STRATEGIC LOCATION ISN’T A GUARANTEE OF A BUSINESS TO SURVIVE - Y, Ayuningtyas (CENTRAL ASIA AND THE CAUCASUS, 2022)
To build a business is not only based on the analysis of the target market, but must be accompanied by a very mature plan. The emergence of new businesses is the toughest challenge today for old businesses. They compete for consumers, so this causes changes in consumer behavior. It can be said that currently there are no more loyal consumers of a product brand. One of the factors that influence a consumer's repurchase of a product brand is location. Determining a strategic location is one of the considerations for consumers to repurchase a product. This study was conducted to describe that a strategic location is not always a guarantee for the sustainability of a business. Sometimes businesses with locations that are difficult to reach become attractive destinations for consumers, especially consumers who have made purchases before. The method used in this study uses a descriptive method, namely by analyzing in depth why the location factor can be considered by potential consumers to make a purchase.